2016
DOI: 10.1111/aos.13008
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intravitreal bevacizumab for zone‐II retinopathy of prematurity

Abstract: Recurrence of neovascularization with bevacizumab monotherapy seems to be higher than that with conventional laser therapy among infants with Type 1 ROP in zone II ROP but reinjection of bevacizumab causes regression in most recurrent cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 16 publications
2
36
0
2
Order By: Relevance
“…(Tolentino, 2011) An increasing number of case series of either bevacizumab or ranibizumab treatment, usually in combination with laser but sometimes as monotherapy, have been reported (Micieli et al, 2009, Wallace and Wu, 2013, Mititelu et al, 2012. There have now been (Autrata et al, 2012, Karkhaneh et al, 2016, Kong et al, 2015b, Mintz-Hittner et al, 2011, Moran et al, 2014 five randomized trials of anti-VEGF agents as treatment for ROP published (Autrata et al, 2012, Karkhaneh et al, 2016, Kong et al, 2015b, Mintz-Hittner et al, 2011, Moran et al, 2014.These trials have small numbers of patients and several have design flaws. They cannot at this point be viewed as providing conclusive data on the ocular and systemic outcomes of the premature infants treated.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…(Tolentino, 2011) An increasing number of case series of either bevacizumab or ranibizumab treatment, usually in combination with laser but sometimes as monotherapy, have been reported (Micieli et al, 2009, Wallace and Wu, 2013, Mititelu et al, 2012. There have now been (Autrata et al, 2012, Karkhaneh et al, 2016, Kong et al, 2015b, Mintz-Hittner et al, 2011, Moran et al, 2014 five randomized trials of anti-VEGF agents as treatment for ROP published (Autrata et al, 2012, Karkhaneh et al, 2016, Kong et al, 2015b, Mintz-Hittner et al, 2011, Moran et al, 2014.These trials have small numbers of patients and several have design flaws. They cannot at this point be viewed as providing conclusive data on the ocular and systemic outcomes of the premature infants treated.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The primary outcome was serum free VEGF and IGF-1 concentrations to 90 days. Karkhaneh and colleagues (2016), in a study from Iran, enrolled 79 infants with zone II, stage 2 or 3 plus ROP (Karkhaneh et al, 2016). The details of randomisation are uncertain and the primary outcome was treatment failure by 90 weeks PMA; this occurring in 9/43 treated with bevacizumab and 1/36 treated with laser (Karkhaneh et al, 2016).…”
Section: Beat-rop Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, the scarring has little impact on the peripheral visual fields in the children (Cryotherapy for Retinopathy of Prematurity Cooperative Group, 2001; Fielder et al, 2015; Harvey et al, 1997; Holm et al, 2015; Larsson et al, 2004; Quinn et al, 2011). Treatment by injection of an antibody against vascular endothelial growth factor (VEGF), which can also cause the abnormal vasculature to resolve, is coming into use; this treatment does not produce peripheral scars (Arambulo et al, 2015; Cayabyab and Ramanathan, 2016; Jefferies, 2016; Karkhaneh et al, 2016; Mintz-Hittner et al, 2016; Quinn and Darlow, 2016). Interestingly, the occurrence of significant ametropia appears to be lower in anti-VEGF treated eyes (Chen et al, 2014; Geloneck et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Karkhaneh et al [23] reported that there were remaining avascular areas in the peripheral retina of 45% of the infants at 90 weeks postmenstrual age after IVB treatment and 10.5% of the infants who received retreatment. On the other hand, Han et al [24] applied two different doses (0.25 and 0.625 mg) of bevacizumab for treatment of ROP, and they found that nearly full vascularization might be achieved without recurrence or additional treatment.…”
Section: Discussionmentioning
confidence: 99%